2021
DOI: 10.3390/cancers13143453
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathways and Druggable Targets in Head and Neck Squamous Cell Carcinoma

Abstract: Head and neck cancers are a heterogeneous group of neoplasms, affecting an ever increasing global population. Despite advances in diagnostic technology and surgical approaches to manage these conditions, survival rates have only marginally improved and this has occurred mainly in developed countries. Some improvements in survival, however, have been a result of new management and treatment approaches made possible because of our ever-increasing understanding of the molecular pathways triggered in head and neck… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 223 publications
0
15
0
Order By: Relevance
“…Phosphorylated MAPK translocates into the nucleus, phosphorylating various transcription factors that trigger the expression of distinct target genes, which advocates proliferation, differentiation, migration, invasion, angiogenesis and metastasis in HNSCC cells. Aberration of EGFR signal activation can bring about disruption of cancer cell homeostasis [57][58][59].…”
Section: Egfr Pathwaymentioning
confidence: 99%
“…Phosphorylated MAPK translocates into the nucleus, phosphorylating various transcription factors that trigger the expression of distinct target genes, which advocates proliferation, differentiation, migration, invasion, angiogenesis and metastasis in HNSCC cells. Aberration of EGFR signal activation can bring about disruption of cancer cell homeostasis [57][58][59].…”
Section: Egfr Pathwaymentioning
confidence: 99%
“…A Phase I immuno-radiotherapy with cetuximab and avelumab (Bavencio), a PD-L1 inhibitor, showed that cetuximab-RT plus avelumab is feasible in patients with advancedstage HNSCC who are not good candidates for cisplatin treatment. Tumour recurrence was 50% after a median of 12 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) months follow-up [244]. Patients are currently being recruited in a Phase I clinical trial to assess the feasibility of intratumoural administration of ipilimumab monotherapy prior to surgical resection, and to assess the immune system response to treatment (NCT02812524).…”
Section: Host Immunitymentioning
confidence: 99%
“…Understanding of these current and emerging therapies for HNSCC necessitates a sound understanding of the signaling pathways involved in these cancers. For this, readers are directed to earlier papers detailing the molecular landscape, oncological pathways and druggable targets for head and neck cancers [22,23]. This review is intended to act as a coherent comprehensive summary of current and emerging molecular therapies for head and neck cancers (HNC).…”
Section: Introductionmentioning
confidence: 99%
“…Substantial expression of PD‐L1 could be observed in the keratinocytes of oral lichen planus (OLP) 10 and oral leukoplakia (OLK), 11 and the increased PD‐L1 level was positively correlated with the malignant transformation of OLK within 5 years 12 . In addition, some studies discussing the role of immune checkpoint biomarkers in OSCC also inferred that the expression of PD‐L1 in OSCC samples was correlated with increased progression and decreased survival rates, though more precise evidence is needed 9,13,14 …”
Section: Introductionmentioning
confidence: 99%
“…12 In addition, some studies discussing the role of immune checkpoint biomarkers in OSCC also inferred that the expression of PD-L1 in OSCC samples was correlated with increased progression and decreased survival rates, though more precise evidence is needed. 9,13,14 Previous studies showed that the infection of C. albicans could induce upregulation of PD-L1 on T cells and natural killer cells. 15,16 Besides, the pathogen-associated molecular patterns (PAMPs) and candidalysin of C. albicans could activate Toll-like receptors (TLR2/ TLR4) on innate immune cells 17 and epidermal growth factor receptor (EGFR) on oral epithelial cells, 18 respectively.…”
mentioning
confidence: 99%